Pragmatic Competence in Early Language Acquisition: A Speech Act Analysis of Children with Speech Delay - Komang Dian Puspita Candra; I Made Yogi Marantika; Ni Putu Cahyani Putri Utami (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
Speech delay is a language development condition that affects children’s verbal communciation abilities. Previous research involving children with speech delays has largely focused on their phonological and lexical development, studies on pragmatic competence specifically how these children perform speech acts during language acquisition remain relatively limited. Therefore, this study aims to analyze the types of speech acts and the functions of speech acts used by children with speech delay in language acquisition process. The study focuses on the utterances of three children aged 2-3 years old who are diagnosed with expressive speech delay. Data were collected through observation, video recording, field notes, and interviews with parents. The data were then analyzed qualitatively using Speech Act theory from Searle (1979) and Context situation theory from Halliday & Hasan (1989). The results of the study show that children with speech delay use three types of speech acts in their language learning process, namely directive (40%), expressive (16%) and representative (44%). The use of representative speech acts are dominantly. At the locutionary level, the speech form used appears incomplete, but at the illocutionary level, its communicative function is complete since they also use facial expressions and gestures to convey their communicative intentions. These findings indicate that pragmatic competence can develop despite limited phonological and lexical abilities. Therefore, language intervention for children with speech delay should target not only vocabulary and articulation but also speech act functions, contextual interpretation, and multimodal communication.